Hamka's Perspective on Parenting to Support Character Building: A Humanist Islamic Approach (Program Studi Pendidikan Agama Islam, 2024)
This article discusses the integration of Hamka's thought and concept of Humanist Islam in the context of childcare and applies it practically to shape children's character according to Humanist Islamic values. The basic assumption of this study is that the integration of Hamka's thought and Humanist Islam offers a holistic approach to shaping children's character, recognizing their spiritual, moral, and social needs. The method used in this study is qualitative, utilizing a comparative and holistic approach as the analytical tool. The findings reveal that Hamka views the role of parents as the main key in shaping children's character. The basic concept of Humanist Islam, with its emphasis on human values, can be applied in parenting to form a balanced and ethical character. The relevance of Hamka's concept of character proves significant in dealing with the dynamics of modern children's lives. Overall, the integration of Hamka's thought and Humanist Islam provides a solid and empowering framework for shaping children's character while remaining relevant in the face of modern life's challenges. Additionally, the concept of Humanist Islam has significant implications in childcare practices, especially within the Indonesian national education system, influencing learning methods, curriculum, and the attitudes of the educational environment. This shapes children to be quality, inclusive, and tolerant individuals. This research contributes to providing a theoretical and practical foundation for parents, educators, and related parties to understand, implement, and develop empowered parenting strategies.